The significance of Electronic Medical Records (EMR) Implementation during covid-19 outbreaks. - Nik Ariffin , Nik Azliza; Ahmad Kamal, Jannatul Iza; Md Jali, Jafalizan; Syamsurianshah; Yastori (Journal of Islamic, Social, Economics and Development, 2024)
The current healthcare framework should be adapted to enhance its efficiency, while also achieving a reduction in healthcare expenditures. By putting modern technology into practice, healthcare providers' workloads will be reduced, information accessibility and flexibility for licensed professionals will increase, and patients will be better equipped to control their lifestyle and health. Having Electronic Medical Records (EMR) and other digital technologies removes the barrier of physical location to care delivery and knowledge exchange. Since so many patients have been admitted during this pandemic and some are being advised to self-quarantine indoors, EMR may be employed in particular to control the symptom history and analysis.